Correlation of Blood Glucose Levels, Uric Acid, and Lipid Profile with Hand Grip Strength: The Role of Age as A Control Variable - Clement Drew; Zita Atzmardina; Alexander Halim Santoso; Fiona Valencia Setiawan (Universitas Malahayati, 2026)
ABSTRACT Handgrip strength (HGS) is an essential biomarker of muscle strength and physical health, with links to illnesses like cardiovascular disease, metabolic syndrome, and frailty. It is particularly important in aging populations, where physical strength promotes independence and quality of life. Blood glucose, uric acid, and lipid profiles all impact metabolic health, influencing physical performance. Elevated glucose levels, disturbed uric acid metabolism, and aberrant lipid profiles lead to impaired muscle function and increased cardiovascular risk. When combined with age-related alterations such as sarcopenia and metabolic dysregulation, these markers have an even greater impact on HGS. This study investigates the association between these metabolic markers and HGS, hypothesizing that aberrant profiles are associated with lower HGS, independent of age. This cross-sectional study in West Jakarta included 120 adults tested for handgrip strength, hemoglobin, blood sugar, uric acid, cholesterol, HDL, LDL, triglycerides, and the triglycerides-to-HDL ratio. Results showed positive correlations between HGS and hemoglobin, hematocrit, and blood sugar, highlighting their roles in oxygen transport and energy provision. The triglycerides-to-HDL ratio also correlated positively with HGS, indicating the influence of lipid metabolism on muscle performance. Age showed an inverse correlation with HGS, consistent with sarcopenia. This study examines the relationship between physiological factors and handgrip strength in the elderly, stressing the importance of optimizing hemoglobin, blood sugar, and cholesterol levels. Limitations include a cross-sectional design and gender bias, necessitating a long-term, comprehensive future study. Keywords: Aging, Handgrip Strength, Lipid Profile, Metabolic Health, Sarcopenia.